Tinjauan Yuridis Hak dan Kewajiban Pasien Sebagai Konsumen dalam Pelayanan Medis - Anggraeni Endah Kusumaningrum (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
Health as one of essential human alongside clothing, food and board. Humanlife become without meaning if sick because human that is sick can never be able to make activity daily favorably. Therefore every sick or patient sure need treatment and doctor's surgery so that oneself again. A relationship between doctor and patient cause therapeutic transaction namely something transaction or agreement to determine therapy or providing service healing. With the existence of therapeutic transaction so have rightsand obligation to both that should be protected. Such as those which organized in UU.Number 8 Years 1999 about Protection consumer UU Number 36 Year 2009 aboutHealth as well as Nomor Law 29 Yerar 2004 about Practicality Medical.